Policy Fragmentation and Coordination Uncertainty in Indonesia’s Bioethanol Industry Governance - Izmirta Rachman; Andreas Budihardjo Surijah; Eka Ardianto (Universitas Mercu Buana, 2026)
Objectives: This study examines how policy fragmentation and coordination uncertainty influence governance dynamics and managerial decision-making in Indonesia’s fuel-grade bioethanol industry.Methodology: The study adopts an exploratory qualitative approach using semi-structured interviews with bioethanol industry actors, policymakers, and renewable energy researchers. Data were analyzed using grounded theory through thematic analysis and iterative coding procedures.Findings: The findings reveal that policy fragmentation produces multi-layered policy failure, including integration failure, orchestration failure, and enforceability failure, which together produce a pattern of fragmented policy governance. This condition generates coordination uncertainty that leads producers to adopt defensive managerial decisions such as delaying investment, underutilizing production capacity, and diverting to alternative markets. Weak knowledge governance further reinforces these coordination failures.Conclusion: Strengthening cross-ministerial coordination, institutionalized policy learning, and knowledge-based governance mechanisms is essential to reduce uncertainty and improve business certainty in Indonesia’s bioethanol industry within the context of green management and renewable energy transition.